2014
DOI: 10.3390/ijms15045774
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-208b and miR-34a Are Associated with Left Ventricular Remodeling after Acute Myocardial Infarction

Abstract: Left ventricular remodeling after acute myocardial infarction (AMI) is associated with adverse prognosis. It is becoming increasingly clear that circulating miRNAs could be promising biomarkers for various pathological processes in the heart, including myocardial infarction, myocardial remodeling and progression to heart failure. In the present study, a total of 359 consecutive patients were recruited. Plasma samples were collected on admission. Echocardiographic studies were performed during the admission and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 43 publications
1
79
0
6
Order By: Relevance
“…For example, myocardial and circulating miRNA-21 were both associated with the degree of myocardial fibrosis [167]. Several other studies showed associations between circulating miRNAs, including miR-20a, miR208b, and miR-34a, and processes of cardiac remodeling, making them potentially interesting biomarkers [168,169]. The miRNAs, miR-22-3p, miR148b-3p, and miR-409-3p, were also associated with HF [170,171].…”
Section: Looking Beyond Circulating Proteins: Micrornas and Metabolitmentioning
confidence: 99%
“…For example, myocardial and circulating miRNA-21 were both associated with the degree of myocardial fibrosis [167]. Several other studies showed associations between circulating miRNAs, including miR-20a, miR208b, and miR-34a, and processes of cardiac remodeling, making them potentially interesting biomarkers [168,169]. The miRNAs, miR-22-3p, miR148b-3p, and miR-409-3p, were also associated with HF [170,171].…”
Section: Looking Beyond Circulating Proteins: Micrornas and Metabolitmentioning
confidence: 99%
“…Повышенное содержание микроРНК-423-5р у больных с ХСН, вызванной ВКМП, по отношению к группе сравнения может свидетельствовать о кардиальном генезе этой ми-кроРНК и выходом ее в кровоток при повреждении миокарда, что подтверждается недавними работами C. Bauters, E. Nabiałek, L. Goldraich [17][18][19]. По-вышенный уровень микроРНК-34а относительно подгруппы ДГС, возможно, связан с преобладанием процессов ремоделирования ЛЖ после ИМ у паци-ентов группы сравнения [12].…”
Section: оригинальные и обзорные статьиunclassified
“…Подавление экспрессии этой микроРНК приводило к сниже-нию гипертрофии, фиброза, апоптоза стареющих клеток и улучшало восстановление миокарда в мо-дели животных после инфаркта миокарда (ИМ). Также уровень циркулирующей микроРНК-34а может быть использован в качестве прогностиче-ского биомаркера ремоделирования левого желу-дочка (ЛЖ) после ИМ [12]. МикроРНК-208a и 499 являются миокардиоспецифичными.…”
unclassified
“…MiR-208b is characterized as cardiac-specific microRNA in early diagnosis of AMI and where showed a correlation between plasma miR-208b and LV dysfunction after MI. Despite miR-34 family has protective attribute against pathological cardiac remodeling, though overexpression of miR-34a demonstrates induced endothelial cells aging and atherosclerosis [24].…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%